Evaluating irrigation strategies and cultivar response of tomato and pepper under automated drip systems in high tunnel and open field environments in North Dakota - Vishnumolakala, Sai Sri Sravya; Jia, Xinhua; Goodspeed, Ivy Mary; Hatterman-Valenti, Harlene (Frontiers in Agronomy, 2025)
In North Dakota, vegetable production is limited due to cold spring temperatures and a short growing season. High tunnels, also called unheated greenhouses, are commonly utilized to increase air temperature and extend the growing season. Inside high tunnels, optimal irrigation scheduling and precise water management are critical factors to achieve high yields. A remotely controlled drip irrigation system was implemented to deliver precise water amounts based on environmental conditions and crop needs. Irrigation scheduling can be automated by using a soil potential sensor-based drip irrigation system and remotely controlled with real-time data. In this 2022–2023 study, eight tomato (Solanum lycopersicum) and pepper (Capsicum annuum) cultivars were compared inside and outside a high tunnel at the North Dakota State University Horticulture Research Farm near Absaraka, North Dakota. We designed irrigation treatments using management allowable depletion (MAD) at 10% and 30%, and the standard time-based treatment with three replicates. Tomatoes under the 30% MAD treatment showed competitive results both inside (35.97 Mg ha-1) and outside (9.25 Mg ha-1) in 2023. Peppers under the 10% MAD treatment, while not consistently the highest yielding, still yielded respectable results inside (22.23 Mg ha-1) and outside (3.58 Mg ha-1) in 2022. Results also showed that the average fruit diameter and weight were significantly higher under 30% MAD for tomatoes and 10% MAD for green peppers, both inside and outside the high tunnel, respectively. These findings suggest that optimizing irrigation strategies, such as using 30% MAD, can enhance tomato crop productivity and water use efficiency, particularly in controlled environments like high tunnels.